Does the timing of pasture allocation affect rumen and plasma metabolites and ghrelin, insulin and cortisol profile in dairy ewes? - Molle, Giovanni; Gregorini, Pablo; Cabiddu, Andrea; Decandia, Mauro; Giovanetti, Valeria; Sitzia, Maria; Dattena, Maria; Porcu, Cristian; Pasciu, Valeria; Gonzalez-Bulnes, Antonio; Berlinguer, Fiammetta; Cannas, Antonello (Frontiers in Veterinary Science, 2022)
A study was undertaken to assess the impact of the timing of grazing on rumen and plasma metabolites and some metabolic hormones in lactating dairy sheep allocated to an Italian ryegrass (Lolium multiflorum Lam) pasture in spring for 4 h/d. Twenty-four mid lactation Sarda ewes stratified for milk yield, body weight, and body condition score, were divided into four homogeneous groups randomly allocated to the treatments (2 replicate groups per treatment). Treatments were morning (AM, from 08:00 to 12:00) and afternoon pasture allocation (PM, from 15:30 to 19:30). Samples of rumen liquor (day 39) and blood plasma (days 17 and 34 of the experimental period) were collected before and after the grazing sessions. Moreover, on days 11 and 35, grazing time was assessed by direct observation and herbage intake measured by the double weighing procedure. The intake of water-soluble carbohydrates at pasture was higher in PM than AM ewes (P < 0.05). The post-grazing propionic and butyric acid concentration, as measured on day 39, was higher in PM than AM ewes (P < 0.05). The basal level of glucose on day 34 and insulin (on both sampling days) were higher in PM than AM (P<0.05). The opposite trend was detected for non-esterified fatty acids (P<0.05, day 34) and urea (both days). The afternoon grazing session resulted in higher insulin level post-grazing on day 17 in PM ewes (P <0.05). Pasture allocation in the afternoon rather than in the morning decreased plasma concentration of ghrelin (P < 0.01) and cortisol (P < 0.001) on day 17, with a smoothed trend on day 34. To conclude, postponing the pasture allocation to afternoon increased the intake of WSC, favoring a glucogenic pattern of rumen fermentation and a rise of glucose and insulin levels in blood, although these effects were not consistent across the whole experimental period. Moreover, the afternoon grazing decreased the level of cortisol and ghrelin, suggesting a higher satiation-relaxing effect.